PREVALENCE OF POLYGLANDULAR AUTOIMMUNE SYNDROME TYPE III IN A GROUP OF ADULTS WITH THYROID DISEASES AND DIABETES MELLITUS - Adriana, Gherbon (European Scientific Journal, ESJ, 2013)
Polyglandular autoimmune syndrome (PAS) is made up of a group of autoimmune disorders of the endocrine glands. Polyglandular autoimmune syndrome type III (PAS III) comprises autoimmune thyroiditis, immune-mediated diabetes mellitus, celiac disease, hypogonadism, myasthenia gravis, sarcoidosis, Sjogren syndrome, rheumatoid arthritis, gastric neoplasia, and malabsorption. The purpose of this study is to determine the prevalence of PAS type III in a group of adults with thyroid diseases and diabetes mellitus (DM). The studied group was of 350 cases with an age between 17-79 years. The group of adults was subdivided according to the type of changes in the glycemic balance in 2 subgroups: DM type 1 represented by 60 cases (17.14%) and DM type 2 represented by 290 cases (82.86%). The methods of investigation were represented by clinical, imaging, biochemical, hormonal and immunological parameters.